Manajemen Modal Kerja Pada PD.Sahabat Mebel Di Kecamatan Pemangkat - Wewen Saputra (JURNAL MANAJEMEN MOTIVASI, 2014)
This study presents a description of the working capital management is about the measurement andassessment of the level of efficiency of use of working capital is based on the concept of quantitative(gross working capital) and the projected capital requirements on PD.Sahabat Mebel. The approach taken in this study is a case study, which uses quantitative analysis. For data collection techniques used interview techniques, obsrvasi, and documentation study. The study concluded that the wisdom of PD. Furniture friend in the use of working capital is not efficient. An increase in current assets element can not increase the optimal profit, an increase of 10% in current assets elements intended to improve the return of more than 10%. Working capital turnover is still low, causing the length of time attachment to the working capital.  An increase in current assets element can not increase the optimal profit, an increase of 10% in current assets elements intended to improve the return of more than 10%. Worki ng capital turnover is still low, causing the length of time attachment to the working capital.